2012
DOI: 10.1016/j.vaccine.2012.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three candidate Rift Valley fever vaccines in sheep

Abstract: Rift Valley fever virus (RVFV) is a mosquito-transmitted Bunyavirus that causes high morbidity and mortality among ruminants and humans. The virus is endemic to the African continent and the Arabian Peninsula and continues to spread into new areas. The explosive nature of RVF outbreaks requires that vaccines provide swift protection after a single vaccination. We recently developed several candidate vaccines and here report their efficacy in lambs within three weeks after a single vaccination. The first vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 33 publications
2
87
0
Order By: Relevance
“…The vaccine induced potentially protective (i.e., 1:40), virus neutralizing titers with single vaccination in five of the six animals within 2 weeks pv (Table 1). These results compared favorably with the outcome of recently reported vaccinations using vaccines based on RVFV glycoproteins, such as GnGc VLPs and Gne , de Boer et al 2010, Mandell et al 2010a, Kortekaas et al 2012, Oreshkova et al 2013, as well as a Newcastle disease virus-vectored vaccine (NDFL-GnGc) (Kortekaas et al 2010a, Kortekaas et al 2010b) and virus replicon particles (Dodd et al 2012, Oreshkova et al 2013, some of which have also been reported to elicit neutralizing antibodies with single vaccination in sheep (Kortekaas et al 2010a, Kortekaas, et al 2012, Oreshkova, et al 2013.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The vaccine induced potentially protective (i.e., 1:40), virus neutralizing titers with single vaccination in five of the six animals within 2 weeks pv (Table 1). These results compared favorably with the outcome of recently reported vaccinations using vaccines based on RVFV glycoproteins, such as GnGc VLPs and Gne , de Boer et al 2010, Mandell et al 2010a, Kortekaas et al 2012, Oreshkova et al 2013, as well as a Newcastle disease virus-vectored vaccine (NDFL-GnGc) (Kortekaas et al 2010a, Kortekaas et al 2010b) and virus replicon particles (Dodd et al 2012, Oreshkova et al 2013, some of which have also been reported to elicit neutralizing antibodies with single vaccination in sheep (Kortekaas et al 2010a, Kortekaas, et al 2012, Oreshkova, et al 2013.…”
Section: Discussionsupporting
confidence: 62%
“…Strategies to develop RVFV vaccines include subunit (Schmaljohn et al 1989, Mandell et al 2010a, DNA (Spik et al 2006), viruslike particles (VLPs) , de Boer et al 2010, Kortekaas et al 2012, virus replicon particles (Kortekaas et al 2011, Dodd et al 2012, Oreshkova et al 2013), virus-vectored (Wallace et al 2006, Heise et al 2009) modified live vaccines, developed from recombinant viruses engineered using reverse genetics (Ikegami et al 2006, Bird et al 2008, Billecocq et al 2008, Habjan et al 2008, Bird et al 2011, live attenuated (Smithburn 1949, Caplen et al 1985, Muller et al 1995, Dungu et al 2010, Pittman 2012, Morrill et al 2013, and inactivated whole virus vaccines (Pittman et al 2000). Although subunit vaccines for RVFV are generally considered safe, and recently some progress has been made in their development, evaluation of immunogenicity and/or efficacy in a target species, sheep, has been performed for a few candidates (Kortekaas et al 2012, Oreshkova et al 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is an urgent need for countermeasures to cope with RVFV that has been accidentally or intentionally introduced into non-endemic countries or regions. RVF vaccines used for animal vaccination in the endemic areas mainly include live-attenuated vaccines (Caplen et al, 1985;Muller et al, 1995;Kortekaas, 2014), inactivated vaccines (Randall et al, 1962;Rusnak et al, 2011), and genetically engineered vaccines (Kortekaas et al, , 2012López-Gil et al, 2013). These vaccines have inherent drawbacks, and no RVF vaccines for human use have been approved by the U.S. Food and Drug Administration.…”
Section: Introductionmentioning
confidence: 99%
“…Neutralizing antibodies are primarily responsible for protection against RVFV-infection [16]. However, one of six lambs treated with an inactivated vaccine showed a reduction in viremia and lack of clinical symptoms although detectable neutralizing antibodies were missing at the time of infection [17]. Furthermore, a study on Crimean-Congo hemorrhagic fever virus (CCHFV, family Bunyaviridae, genus Nairovirus) reports that an inactivated vaccine is able to elicit a considerable T-cell reaction in humans as measured by IFN-gamma production [18].…”
Section: Discussionmentioning
confidence: 98%